EDUCATIONAL AND AESTHETIC SIGNIFICANCE OF UZBEKISTAN MUSICAL HERITAGE - Qo‘ziyev Toyir Asqarovich (Bright Mind Publishing, 2025)
This article examines the educational and aesthetic significance of Uzbekistan’s rich musical heritage, including traditional maqom, folk songs, and instrumental melodies. It explores how music serves as a bridge between generations, fosters a sense of beauty, promotes humanism, and instills moral values. The role of music as an educational tool is revealed through oral folk traditions, maqom art, and national instruments. Special attention is given to the importance of Uzbek music in shaping a well-rounded and spiritually enriched individual.
Keywords: Uzbek musical heritage, maqom art, oral folk tradition, educational significance, aesthetic values, national instruments, spiritual and moral upbringing, music aesthetics, cultural heritage, youth education.